2017
DOI: 10.1088/1361-6528/aa7ba9
|View full text |Cite
|
Sign up to set email alerts
|

Hot-pressed polymer nanofiber supported graphene membrane for high-performance nanofiltration

Abstract: Graphene oxide (GO) sheets can be readily surface-overlaid on hot-pressed electrospun polyacrylonitrile (PAN) nanofiber membrane to form a continuous and crack-free layer; upon thermal reduction at 150 °C for 12 h, the resulting reduced GO (rGO) layer can reject ∼90% MgSO with high water flux (due to the size exclusion mechanism), making the prepared PAN-rGO membranes promising nanofiltration media for water purification. It is important to note that no delamination of GO/rGO sheet layers has been observed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The blue dashed line is a proxy for complete salt exclusion. Novel materials assessed were nanotubes, 139-142 2-D laminates, 29,[143][144][145][146][147][148] biomimetic channels, [149][150][151][152][153][154] and nanoporous sheets. 155,156 Energy & Environmental Science Perspective Open Access Article.…”
Section: Pressure-driven Desalination: Reverse Osmosismentioning
confidence: 99%
“…The blue dashed line is a proxy for complete salt exclusion. Novel materials assessed were nanotubes, 139-142 2-D laminates, 29,[143][144][145][146][147][148] biomimetic channels, [149][150][151][152][153][154] and nanoporous sheets. 155,156 Energy & Environmental Science Perspective Open Access Article.…”
Section: Pressure-driven Desalination: Reverse Osmosismentioning
confidence: 99%
“…Electrospun fiber membranes are often employed as supports for thin film composite membranes for RO and NF desalination but the high surface roughness of electrospun membranes can complicate their utilization as supports for NATMs . For example, when Wang et al prepared multilayer GO membranes by vacuum deposition of GO flakes onto electrospun poly‐acrylonitrile membranes, they observed that GO layers developed multiple cracks upon drying. Hot pressing of the electrospun poly‐acrylonitrile membranes prior to GO deposition allowed mitigating the surface roughness and, as a result, uniform GO layers were obtained …”
Section: Blending Traditional Membrane Fabrication Techniques With 2dmentioning
confidence: 99%
“…For example, when Wang et al prepared multilayer GO membranes by vacuum deposition of GO flakes onto electrospun poly‐acrylonitrile membranes, they observed that GO layers developed multiple cracks upon drying. Hot pressing of the electrospun poly‐acrylonitrile membranes prior to GO deposition allowed mitigating the surface roughness and, as a result, uniform GO layers were obtained …”
Section: Blending Traditional Membrane Fabrication Techniques With 2dmentioning
confidence: 99%
“…Specifically, research on PAN nanocomposite fibers in sensors, supercapacitor, batteries, electromagnetic interference (EMI) shielding, metal ion removal, and antimicrobial relevance is reviewed. 810 These applications need to optimize the nanofiber chemical composition, surface porosity, hydrophobicity, absorption capacity, and wettability. And future scenarios in the technological development of these nanocomposite fibers are presented.…”
Section: Introductionmentioning
confidence: 99%